Approximation of electro-optical characteristics of ChLC at transitions from the homeotropic texture - Rybalochka, A.; Chumachkova, M.; Sorokin, V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
In this paper a method for an approximation of electro-optical characteristics of a cholesteric liquid crystal (ChLC) that describe behavior of a cholesteric material at transitions from the field induced homeotropic texture to the stable planar and focal conic textures have been proposed. To obtain the complete information about such behavior of a cholesteric liquid crystal a protracted experimental research is required. Proposed method allows to obtain all necessary approximated electro-optical characteristics of a cholesteric liquid crystal on the basis of experimental measuring only of four special electro-optical characteristics.